Implementasi Metode Diskusi Pada Materi Past Tense Nominal dan Verbal Dalam Pembelajaran Bahasa Inggris di SMAN 5 Pekanbaru - Hendri Kurniawan; Vitriani Vitriani; Tengku Muhammad Hanafi (Jurnal Masyarakat Mengabdi Nusantara, 2024)
This activity aims to explore and apply the effectiveness of the discussion method in learning English at SMAN 5 Pekanbaru, with a specific focus on past tense nominal & verbal topics. the school faces challenges related to the adequacy of educators in their respective fields, including english language teachers. in this study, teachers not only serve as instructors but also actively facilitate the discussion sessions.the research methodology encompasses planning, execution, and evaluation of discussion activities in the x6 class at sman 5 pekanbaru. direct observations are conducted to monitor student participation during the discussion sessions, while teachers provide constructive feedback on the implementation of the discussion method. students are also interviewed to gather their perspectives on the effectiveness of this method in understanding past tense nominal & verbal.the hope is that the results of this research will provide a comprehensive overview of how the discussion method can enhance english language learning at SMAN 5 pekanbaru, specifically focusing on past tense nominal & verbal topics. the implications of this research are expected to contribute valuable insights to the development of innovative learning strategies at the secondary school level.